Unearthing Prehistory: The Archaeology of Northeastern Luzon, Philippine Islands - Corny, Julien; Zanolli, Clemént; Villier, Boris (Hukay, 2014)
Unearthing Prehistory: The Archaeology of Northeastern Luzon, Philippine Islands by Armand Salavador Mijares